Partnering with Local Hospitals and Public Health to Manage COVID‐19 Outbreaks in Nursing Homes. Issue 1 (14th October 2020) - Montoya, Ana; Jenq, Grace; Mills, John P.; Beal, Jennifer; Diviney Chun, Erin; Newton, Duane; Gibson, Kristen; Mantey, Julia; Hurst, Kristen; Jones, Karen; Mody, Lona
Abstract : BACKGROUND/OBJECTIVES: Almost half of deaths related to COVID‐19 in the United States are linked to nursing homes (NHs). We describe among short‐term and long‐term residents at three NHs in Michigan the outbreak identification process, universal testing, point prevalence of COVID‐19, and subsequent containment efforts, outcomes, and challenges. DESIGN: Outbreak investigation. SETTING: Three NHs in southeast Michigan. PARTICIPANTS: All residents ( N = 215) at three NHs (total beds = 356) affiliated with a large academic healthcare system. METHODS: Upon detection of confirmed cases within the facility, each NH in collaboration and consultation with local hospital, public health officials, and parent corporation implemented immediate facility‐wide testing and the following intervention measures: cohorting of COVID‐19 positive residents; communication regarding testing and results with residents, healthcare professionals, and families; personal protective equipment reeducation and use throughout facilities; and dedicated staffing for infected patients cohorted in a dedicated COVID‐19 wing. We collected patient data regarding demographics, symptoms, comorbidities, hospitalization, and 14‐day outcomes. RESULTS: A total of 29 cases of COVID‐19 were identified at three participating NHs. Nineteen cases of COVID‐19 were identified through symptom‐triggered testing from March 23 to April 23, 2020; 10 (4.7%) additional cases were identified through universal testing of 215 residents conducted from April 7 to 15, 2020. The hospitalization rate was 37.9%. The case fatality rate was 20.7% (6/29); these patients had multiple comorbidities. No residents who tested positive through the point‐prevalence survey required hospitalization, and five were discharged home within 14 days. CONCLUSION: Proactive and coordinated steps between NH medical directors and administrators, referral hospitals including their laboratories, and local public health officials are necessary to rapidly respond to an outbreak and limit the transmission of COVID‐19. This coordinated public health approach may save lives, minimize the burden to the healthcare system, and reduce healthcare costs. Abstract : See related editorial by Kathleen Unroe